Characterization of Y3(Al,Ga)5O12:Ce3+ phosphor thin films prepared by pulsed laser deposition - Dlamini, Sipho Thapo Solomon (University of the Free State, 2013)
The morphological and luminescent properties of Y3(Al,Ga)5O12:Ce3+ powder phosphor were investigated. Scanning Electron Microscopy (SEM) revealed the phosphor’s agglomerated particles with a size ranging from 0.4μm to 1.4μm. The X-ray diffraction (XRD) indicated a cubic polycrystalline phosphor with an average crystal size of 80 nm. Excitation peaks for the powder were obtained at 439, 349, 225 and 189 nm and emission peaks at 512 and 565 nm. Emission wavelength at 512 nm was also used to approximate the Al/Ga ratio within the crystal. Photoluminescence (PL) data also revealed that the addition of the Ga into the YAG:Ce3+ matrix caused a blue-shift in the emission spectra. The UV-VUV excitation and emission spectra of the Y3(Al,Ga)5O12:Ce3+ were also recorded and an energy diagram was constructed from the values. The phosphor powder was used as target material for Pulsed Laser Deposition (PLD). SiO2/Si(100) was used as substrates and thin films were deposited in the presence of different background gases. XRD indicated that better crystallization took place for films deposited in a 20 mTorr O2 atmosphere. Atomic force microscopy (AFM) revealed an RMS value of 0.7 nm, 2.5 nm and 4.8 nm for the films deposited in vacuum, O2 and Ar atmospheres, respectively. The highest PL intensity was observed for films deposited in the O2 atmosphere. The thickness of the films varied from 120 nm to 270 nm with films deposited in vacuum having the thin layer and those in Ar having the thick layer. The stoichiometry of the powder was maintained in the film during the deposition as confirmed by Rutherford backscattering spectroscopy (RBS). Luminescent properties of Y3(Al,Ga)5O12:Ce3+ thin films prepared by PLD at different substrate temperatures in an O2 background atmosphere were also investigated. XRD indicated that the films have the same cubic polycrystalline phase structure as the powder. AFM revealed poorly defined grain growth for films ablated at a substrate temperature of 22°C and 500°C but well defined grain growth was observed for films ablated at a 300°C substrate temperature. Auger electron spectroscopy (AES) depth profile of the film ablated at 500°C indicated that Si has diffused into the thin film. The highest PL intensity was observed for films deposited at the substrate temperature of 300°C. A slight shift in the wavelength of the PL spectra was obtained for the thin films with respect to the powder due to a change in the crystal field. The maximum PL intensity was obtained from the film deposited at the substrate temperature of 300⁰C in an O2 atmosphere. In addition, the films with well-defined grains (rougher surfaces) showed higher PL intensity compared to films with poorly-defined grains (smooth surfaces) as confirmed from AFM data
Dissertation (M.Sc. (Physics))--University of the Free State, 2014
Keywords: Photoluminescence; Pulsed laser deposition; Phosphors; Thin films; Y3(Al,Ga)5O12:Ce3+; Different gas atmospheres; Substrate temperature